Formation of Large Native Sulfur Deposits Does Not Require Molecular Oxygen - Labrado, Amanda L.; Brunner, Benjamin; Bernasconi, Stefano M.; Peckmann, Jörn (Frontiers in Microbiology, 2019)
Large native (i.e. elemental) sulfur deposits can be part of caprock assemblages found on top of or in lateral position to salt diapirs and as stratabound mineralization in gypsum and anhydrite lithologies. The native sulfur is formed when hydrocarbons (i.e. oil or methane) come in contact with sulfate minerals in presence of liquid water. The prevailing concept for native sulfur formation in such settings is sulfide produced by sulfate-reducing bacteria is oxidized to zero-valent sulfur in presence of molecular oxygen (O2). Although possible, such a scenario is problematic because: 1. exposure to oxygen would inhibit microbial sulfate reduction, removing the process that produces sulfide; 2. excess supply with oxygen would convert sulfide into sulfate rather than native sulfur; and 3. to produce large native sulfur deposits, enormous amounts of oxygenated water would need to be brought in close proximity to environments in which ample supply of hydrocarbon sustains sulfate reduction. Stable sulfur isotope data from native sulfur deposits emplaced at a stage after the formation of the host rocks indicate that the sulfur was formed in a setting that had little solute exchange with the ambient environment instead of a system with ample supply with dissolved oxygen. Hence, we deduce that there must be a process for the formation of native sulfur in absence of an external oxidant for sulfide. We hypothesize that accumulation of sulfide in a system with restricted fluid exchange triggers a shift from harmful sulfide to nonhazardous native sulfur production, and that sulfate-reducing organisms, possibly in cooperation with other anaerobic microbial partners, take advantage of this modification of the sulfate reduction process when exposed to sulfide stress. We demonstrate that such a process is thermodynamically feasible and argue that there is evidence that microbes form native sulfur deposits in absence of light and external oxidants such as O2, nitrate, or metal oxides.